Nano-based carbon dioxide corrosion resistant cement paste and preparation method thereof

By introducing nano-based inert materials and anti-corrosion materials into the cement slurry, the nano-based anti-carbon dioxide corrosion slurry is formed, which solves the problem of poor corrosion resistance of existing cement slurry under high concentration CO2 formation conditions, and achieves the effect of high density, low permeability and strength of cement stone without decay.

CN119774921APending Publication Date: 2025-04-08CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311293277.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The corrosion resistance of existing cement slurry under high concentration CO2 formation conditions is not ideal, resulting in a decrease in the compressive strength of cement stone and an increase in permeability, which seriously affects the safety of downhole casing and its operating tools.

Method used

Nano-based anti-carbon dioxide corrosion slurry is used, and its raw materials include cement, active materials, non-permeable materials, nano-based inert materials, anti-corrosion materials, etc. Through specific formulation and stirring processes, cement slurry with high density, low permeability, strength without decline and corrosion resistance is formed.

Benefits of technology

It effectively improves the corrosion resistance of cement slurry under high concentration CO2 formation conditions, ensures the compressive strength and density of cement stone, reduces permeability, and meets the performance indicators of cementing technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of cement paste, in particular to nano-based carbon dioxide corrosion resistant cement paste and a preparation method thereof.The nano-based carbon dioxide corrosion resistant cement paste is obtained according to the following method that firstly, cement, an active material, a non-permeable material, a lightening material, a weighting material, a nano-based inert material and an anti-corrosion material are evenly mixed to obtain a solid mixture; adding the filtrate reducer, the retarder, the dispersing agent and the defoaming agent into water, uniformly mixing to obtain a mixed solution, and finally, adding the solid mixture into the mixed solution, and uniformly mixing to obtain the drilling fluid. The nano-based carbon dioxide corrosion-resistant cement paste disclosed by the invention has the excellent performances of adjustable density, low permeability, non-declining strength and corrosion resistance, and effectively solves the problem that cement paste and set cement cannot meet the operation requirements under the complicated formation conditions of CO2 oil displacement, CO2 burying and the like in the high-concentration CO2 formation well cementation and secondary oil recovery processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement slurry, in particular to nano-based carbon dioxide corrosion resistant cement slurry and a preparation method thereof. Background Art

[0002] With the development of deep acidic gas reservoirs, the application of CO2 flooding and CO2 storage technologies in secondary oil recovery, cementing operations often face complex environments with high-concentration CO2 formations, which leads to reduced compressive strength of cement stone, increased permeability, and loss of cementing components in cement, which destroys the structural integrity of cement stone. In severe cases, it can lead to long-term exposure, corrosion, perforation, and even fracture of downhole casing and various operating tools, bringing many adverse effects to the safe production of oil and gas wells.

[0003] At present, in the face of the problem of CO2 corrosion on cementing cement, relevant anti-corrosion measures are mainly established by preventing the corrosive medium from penetrating into the cement, changing the calcium-silicon ratio, reducing the cement alkalinity, and improving the corrosion resistance of the cement material itself. Foreign countries mainly solve the relevant corrosion problems by improving the acid corrosion resistance of the cement material itself and reducing the void structure of the cement, such as Schlumberge's special anti-corrosion agent to form XP-1 corrosion-resistant cement slurry, Dowell's CO2 corrosion-resistant cement and Halliburton's special anti-corrosion cement (FLEXCEM). In recent years, a large number of research projects on the acid corrosion resistance of cement stone have been carried out in China, mainly focusing on using inert anti-corrosion materials of a certain particle size to replace cementing cement clinker or adding latex microspheres to improve the corrosion resistance of cement stone. The above methods have all exerted a certain anti-corrosion effect, but there are still shortcomings. Their anti-corrosion performance for complex formations with high CO2 acid gas content is not ideal. Summary of the invention

[0004] The present invention provides a nano-based carbon dioxide corrosion resistant cement slurry and a preparation method thereof, which overcomes the deficiencies of the above-mentioned prior art and can effectively solve the problem of poor anti-corrosion performance of the existing cement slurry.

[0005] The technical scheme of the present invention is achieved through the following measures: a nano-based carbon dioxide corrosion resistant cement slurry, wherein the raw materials, by weight, include 100 parts of cement, 5.0 to 10.0 parts of active materials, 5.0 to 20.0 parts of non-permeable materials, 0 to 20.0 parts of lightening materials, 0 to 5.0 parts of weighting materials, 5.0 to 20.0 parts of nano-based inert materials, 10.0 to 30.0 parts of anti-corrosion materials, 5.0 to 6.0 parts of fluid loss reducer, 1.0 to 3.0 parts of retarder, 1.0 to 2.0 parts of dispersant, 0.5 to 1.0 parts of defoaming agent and 43.0 to 64.0 parts of water.

[0006] The following are further optimizations and / or improvements to the above technical solutions: The above cement is oil well G grade medium sulphur and hydrochloric acid resistant cement.

[0007] The active material is microsilica powder with a particle size of 1 μm to 20 μm.

[0008] The non-permeable material is ultra-fine cement, which is composed of 50% to 70% by mass of cement with a particle size distribution of 10μm to 15μm and the remainder of cement with a particle size distribution of 30μm to 35μm.

[0009] The above-mentioned lightening material is one or more of glass beads, diatoms and soil.

[0010] The above-mentioned weighting material is one or more of barite, iron ore powder and manganese oxide.

[0011] The nano-based inert material is a mixture of silicon dioxide and graphene oxide in a mass ratio of (45 to 60): (40 to 55).

[0012] The above-mentioned anti-corrosion material is one or more of sodium borosilicate fiber, latex powder and rubber.

[0013] The above-mentioned fluid loss reducer is one or more of amine-modified humic acid compounds, organosilicon humic acid amide compounds, and sulfonated olefin styrene compounds.

[0014] The amine-modified humic acid compound is sulfonated lignite SMC, the organosilicon humic acid amide compound is humic acid silicon, and the sulfonated olefin styrene compound is sulfonated olefin styrene compound BXF-200L.

[0015] The retarder is one or more of wood sulfonate compounds, hydroxycarboxylic acids and salt compounds thereof.

[0016] The above-mentioned lignosulfonate compound is the lignosulfonate compound HR-4, and the hydroxycarboxylic acid and its salt compound is the hydroxycarboxylic acid and its salt compound FS-31L and the hydroxycarboxylic acid and its salt compound FS-35L.

[0017] The above dispersant is one or more of formaldehyde acetone condensation polymer, polynaphthalene sulfonate and amino polymer derivative.

[0018] The formaldehyde acetone polycondensate is formaldehyde acetone polycondensate SXY-2, the polynaphthalene sulfonate is polynaphthalene sulfonate UNF-2, and the amino polymer derivative is melamine sulfonate PMS.

[0019] The defoaming agent is one of polyorganosiloxane or organic phosphate.

[0020] The polyorganosiloxane is polyorganosiloxane CF501, and the organic phosphate is organic phosphate XP-1.

[0021] The nano-based carbon dioxide corrosion resistant cement slurry is obtained by the following method: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding a required amount of fluid loss reducer, retarder, dispersant and defoamer to a required amount of water at a stirring speed of 3800 rpm to 4200 rpm and stirring for 50 s to 70 s to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring for 35 seconds to 40 seconds at a stirring speed of 3800 rpm to 4200 rpm to obtain nano-based carbon dioxide corrosion resistant cement slurry.

[0022] The second technical solution of the present invention is achieved by the following measures: A method for preparing nano-based carbon dioxide corrosion resistant cement slurry is carried out according to the following method: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding a required amount of fluid loss reducer, retarder, dispersant and defoamer to a required amount of water at a stirring speed of 3800 rpm to 4200 rpm and stirring for 50 s to 70 s to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring for 35 seconds to 40 seconds at a stirring speed of 3800 rpm to 4200 rpm to obtain nano-based carbon dioxide corrosion resistant cement slurry.

[0023] The nano-based carbon dioxide corrosion-resistant cement slurry of the present invention has the excellent properties of adjustable density, low permeability, non-fading strength and corrosion resistance, and effectively solves the problem that cement slurry and cement stone cannot meet the operation requirements under complex formation conditions such as high-concentration CO2 formation cementing, CO2 oil displacement in secondary oil recovery, and CO2 storage. DETAILED DESCRIPTION

[0024] The present invention is not limited by the following embodiments, and specific implementation methods can be determined according to the technical scheme of the present invention and actual conditions. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all known and commonly used chemical reagents and chemicals in the prior art; the percentages in the present invention are all mass percentages unless otherwise specified.

[0025] The present invention will be further described below in conjunction with embodiments: Example 1: The nano-based anti-carbon dioxide corrosion cement slurry, the raw materials by weight include 100 parts of cement, 5.0 to 10.0 parts of active materials, 5.0 to 20.0 parts of non-permeable materials, 0 to 20.0 parts of lightening materials, 0 to 5.0 parts of weighting materials, 5.0 to 20.0 parts of nano-based inert materials, 10.0 to 30.0 parts of anti-corrosion materials, 5.0 to 6.0 parts of fluid loss additives, 1.0 to 3.0 parts of retarders, 1.0 to 2.0 parts of dispersants, 0.5 to 1.0 parts of defoaming agents and 43.0 to 64.0 parts of water.

[0026] Example 2: As an optimization of the above example, the cement is a medium-sulfur and hydrochloric acid resistant cement of oil well G grade.

[0027] Embodiment 3: As an optimization of the above embodiment, the active material is microsilica powder with a particle size of 1 μm to 20 μm, wherein the content of silicon dioxide in the microsilica powder is greater than 95%.

[0028] Embodiment 4: As an optimization of the above embodiment, the non-permeable material is ultrafine cement, which is composed of 50% to 70% by mass of cement with a particle size distribution of 10 μm to 15 μm and the remainder of cement with a particle size distribution of 30 μm to 35 μm.

[0029] Embodiment 5: As an optimization of the above embodiment, the lightening material is one or more of glass microspheres, diatoms and soil, wherein the soil can be bentonite.

[0030] Example 6: As an optimization of the above example, the weighting material is one or more of barite, iron ore powder and manganese oxide.

[0031] Embodiment 7: As an optimization of the above embodiment, the nano-based inert material is a mixture of silicon dioxide and graphene oxide in a mass ratio of (45 to 60): (40 to 55), wherein the silicon dioxide particle size is 30 nm to 50 nm, the graphene oxide sheet size is 2 μm to 10 μm, and the oxygen content is 30% to 60%.

[0032] Embodiment 8: As an optimization of the above embodiment, the anti-corrosion material is one or more of sodium borosilicate fiber, latex powder, and rubber, wherein the length of the anti-corrosion material is 5 mm to 10 mm.

[0033] Embodiment 9: As an optimization of the above embodiment, the fluid loss reducer is one or more of amine-modified humic acid compounds, organosilicon humic acid amide compounds, and sulfonated olefin styrene compounds.

[0034] Example 10: As an optimization of the above example, the amine-modified humic acid compound is sulfonated lignite SMC, the organosilicon humic acid amide compound is humic acid silicon, and the sulfonated olefin styrene compound is sulfonated olefin styrene compound BXF-200L.

[0035] Embodiment 11: As an optimization of the above embodiment, the retarder is one or more of wood sulfonate compounds, hydroxycarboxylic acids and salt compounds thereof.

[0036] Example 12: As an optimization of the above example, the lignosulfonate compound is the lignosulfonate compound HR-4, and the hydroxycarboxylic acid and its salt compound is the hydroxycarboxylic acid and its salt compound FS-31L and the hydroxycarboxylic acid and its salt compound FS-35L.

[0037] Example 13: As an optimization of the above example, the dispersant is one or more of formaldehyde acetone condensation product, polynaphthalene sulfonate and amino polymer derivative.

[0038] Example 14: As an optimization of the above example, the formaldehyde acetone condensation product is formaldehyde acetone condensation product SXY-2, the polynaphthalene sulfonate is polynaphthalene sulfonate UNF-2, and the amino polymer derivative is melamine sulfonate PMS.

[0039] Example 15: As an optimization of the above example, the defoaming agent is one of polyorganosiloxane or organic phosphate.

[0040] Example 16: As an optimization of the above example, the polyorganosiloxane is polyorganosiloxane CF501, and the organic phosphate is organic phosphate XP-1.

[0041] Example 17: As an optimization of the above example, a nano-based carbon dioxide corrosion resistant cement slurry is obtained by the following method: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding a required amount of fluid loss reducer, retarder, dispersant and defoamer to a required amount of water at a stirring speed of 3800 rpm to 4200 rpm and stirring for 50 s to 70 s to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring for 35 seconds to 40 seconds at a stirring speed of 3800 rpm to 4200 rpm to obtain nano-based carbon dioxide corrosion resistant cement slurry.

[0042] Embodiment 18: The nano-based carbon dioxide corrosion resistant cement slurry comprises, by weight, 100 parts of oil well G-grade medium sulfuric acid resistant cement, 5.0 parts of active material (microsilica powder), 5.0 parts of non-permeable material (mixed by 50% by weight of cement with a particle size distribution of 10 μm and 50% by weight of cement with a particle size distribution of 30 μm), 5.0 parts of nano-based inert material (a mixture of silicon dioxide and graphene oxide in a mass ratio of 45:40), 10.0 parts of anti-corrosion material (sodium borosilicate fiber), 5.0 parts of fluid loss reducer (sulfonated lignite SMC), 1.0 part of retarder (wood sulfonate compound HR-4), 1.0 part of dispersant (formaldehyde acetone condensate SXY-2), 0.5 part of defoamer (polyorganosiloxane CF501) and 43.0 parts of water, and is obtained by the following method: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding the required amount of fluid loss reducer, retarder, dispersant and defoamer to the required amount of water at a stirring speed of 3800 rpm and stirring for 50 seconds to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring at a stirring speed of 3800 rpm for 35 seconds to obtain nano-based carbon dioxide corrosion resistant cement slurry.

[0043] Embodiment 19: The nano-based carbon dioxide corrosion resistant cement slurry comprises, by weight, 100 parts of oil well G-grade medium sulfuric acid resistant cement, 10.0 parts of active material (microsilica powder), 20.0 parts of non-permeable material (mixed with 70% by weight of cement with a particle size distribution of 15 μm and 30% by weight of cement with a particle size distribution of 35 μm), 20.0 parts of lightening material (glass microspheres), 5.0 parts of weighting material (barite), 20.0 parts of nano-based inert material (a mixture of silicon dioxide and graphene oxide with a mass ratio of 60:55), 30.0 parts of corrosion-resistant material (latex powder), 6.0 parts of fluid loss reducer (humic acid silicon), 3.0 parts of retarder (hydroxycarboxylic acid and its salt compound FS-31L), 2.0 parts of dispersant (polynaphthalene sulfonate UNF-2), 1.0 part of defoamer (organic phosphate XP-1) and 64.0 parts of water, and is obtained by the following method: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding a required amount of fluid loss reducer, retarder, dispersant and defoamer to a required amount of water at a stirring speed of 4200 rpm and stirring for 70 seconds to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring at a stirring speed of 4200 rpm for 40 seconds to obtain nano-based carbon dioxide corrosion resistant cement slurry.

[0044] Embodiment 20: The nano-based carbon dioxide corrosion resistant cement slurry comprises, by weight, 100 parts of oil well G-grade medium sulfuric acid resistant cement, 8.0 parts of active material (microsilica powder), 10.0 parts of non-permeable material (mixed with 60% by weight of cement with a particle size distribution of 10 μm and 40% by weight of cement with a particle size distribution of 30 μm), 10.0 parts of lightening material (diatom), 3.0 parts of weighting material (manganese oxide), 10.0 parts of nano-based inert material (a mixture of silicon dioxide and graphene oxide in a mass ratio of 50:50), 20.0 parts of anti-corrosion material (latex powder), 5.5 parts of fluid loss reducer (sulfonated olefin styrene compound BXF-200L), 2.0 parts of retarder (hydroxycarboxylic acid and its salt compound FS-35L), 1.5 parts of dispersant (melamine sulfonate PMS), 0.8 parts of defoamer (polyorganosiloxane CF501) and 50.0 parts of water, and is obtained by the following method: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding the required amount of fluid loss reducer, retarder, dispersant and defoamer to the required amount of water at a stirring speed of 4000 rpm and stirring for 60 seconds to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring at a stirring speed of 4000 rpm for 35 seconds to obtain nano-based carbon dioxide corrosion resistant cement slurry.

[0045] Compared with the prior art, the present invention has the following advantages: Firstly, active materials (microsilica powder) and non-permeable materials (ultrafine cement) are added to the raw materials of the present invention. Among them, the raw material microsilica powder can generate a new phase of calcium silicate gel structure with Ca(OH)2 in the cement, thereby increasing the content of cementitious components in the mineral components of the cement stone; the raw material ultrafine cement can further improve the particle grading of the cement slurry, so that the cured cement stone exhibits higher density and finer pore size distribution, thereby preventing the invasion of acidic gases.

[0046] Secondly, the raw materials of the present invention are introduced with nano-based inert materials, which are a mixture of silicon dioxide and graphene oxide. The silicon dioxide has a small particle size, a large surface energy, and volcanic ash activity, which can improve the mechanical properties and microstructure of cement-based materials; and the graphene oxide contains a large number of -OH, -COOH and -O- polar groups. The introduction of these active groups increases the distance between graphite sheets and has hydrophilicity, avoiding the interaction with Ca 2+ The complexation results in flocculation, which in turn fully exerts the strengthening and toughening effects.

[0047] Thirdly, the anti-corrosion material is introduced into the raw material of the present invention, and the high-molecular flexible molecular chain segments of the anti-corrosion material can continuously penetrate the microscopic gaps of cement, so that a dense network membrane structure is generated at the cement stone interface after solidification, thereby improving the plasticity of the cement stone and reducing the volume shrinkage of the cement stone.

[0048] Fourthly, the nano-based carbon dioxide corrosion resistant cement slurry obtained by mixing the raw materials in proportion has an adjustable density range, an API filtration loss of less than 50 ml, an easily adjustable thickening time, a 24-hour compressive strength of the solidified cement stone of more than 14.0 MPa, and a strength that does not decay for 30 days, and a permeability of less than 9.0x10 -3 The advantages of mD are outstanding corrosion resistance and its various performance parameters can meet the performance indicators of cementing technology.

[0049] Example 21: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 12.0 parts of active materials, 6.0 parts of non-permeable materials, 16.0 parts of lightening materials, 5.0 parts of nano-based inert materials, 10.0 parts of anti-corrosion materials, 6.0 parts of fluid loss reducers, 3.0 parts of retarders, 2.0 parts of dispersants, 1.0 parts of defoaming agents and 64.0 parts of water, and the selection of remaining raw materials and process steps are the same as those in Example 20.

[0050] Example 22: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 8.0 parts of active materials, 8.0 parts of non-permeable materials, 10.0 parts of lightening materials, 12.0 parts of nano-based inert materials, 16.0 parts of anti-corrosion materials, 5.8 parts of fluid loss reducers, 2.6 parts of retarders, 1.7 parts of dispersants, 1.0 parts of defoaming agents and 57.0 parts of water, and the selection of remaining raw materials and process steps are the same as those in Example 20.

[0051] Example 23: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 7.0 parts of active materials, 10.0 parts of non-permeable materials, 8.0 parts of lightening materials, 19.0 parts of nano-based inert materials, 21.0 parts of anti-corrosion materials, 5.6 parts of fluid loss reducers, 2.1 parts of retarders, 1.3 parts of dispersants, 1.0 parts of defoaming agents and 52.0 parts of water, and the selection of remaining raw materials and process steps are the same as those in Example 20.

[0052] Example 24: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 8.0 parts of active materials, 12.0 parts of non-permeable materials, 4.0 parts of lightening materials, 15.0 parts of nano-based inert materials, 23.0 parts of anti-corrosion materials, 5.4 parts of fluid loss reducers, 2.7 parts of retarders, 1.1 parts of dispersants, 0.5 parts of defoaming agents and 47.0 parts of water, and the selection of remaining raw materials and process steps are the same as those in Example 20.

[0053] Example 25: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 9.0 parts of active materials, 14.0 parts of non-permeable materials, 18.0 parts of nano-based inert materials, 26.0 parts of anti-corrosion materials, 5.2 parts of fluid loss reducers, 2.4 parts of retarders, 1.0 parts of dispersants, 0.5 parts of defoaming agents and 43.0 parts of water, and the selection of remaining raw materials and process steps are the same as those in Example 20.

[0054] Example 26: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 10.0 parts of active material, 16.0 parts of non-permeable material, 4.0 parts of weighting material, 20.0 parts of nano-based inert material, 30.0 parts of anti-corrosion material, 5.0 parts of fluid loss agent, 2.0 parts of retarder, 1.2 parts of dispersant, 0.5 parts of defoaming agent and 40.0 parts of water, and the selection of remaining raw materials and process steps are the same as those in Example 20.

[0055] Comparative Example 1: The difference from Example 20 of the present invention is that the raw material formula is 100 parts of cement, 9.0 parts of active material, 14.0 parts of non-permeable material, 5.2 parts of fluid loss reducer, 2.4 parts of retarder, 0.5 part of defoaming agent and 35.0 parts of water, and the selection of other raw materials and the process steps are the same as those in Example 20.

[0056] Example 27: The nano-based carbon dioxide corrosion resistant cement slurry prepared in Examples 21 to 26 of the present invention was subjected to performance tests, including basic performance and corrosion resistance. Meanwhile, Comparative Example 1 was used as a control. The basic performance results are shown in Table 1, and the corrosion resistance results are shown in Table 2. It can be seen from Table 1 and Table 2 that the nano-based carbon dioxide corrosion resistant cement slurry of the present invention has good engineering performance, and its density is 1.50 g / cm 3 Up to 2.00g / cm3 The range is adjustable, API filtration loss is less than 50ml, the thickening time is easy to adjust, the compressive strength of the solidified cement stone reaches more than 14.0 MPa in 24 hours, and the strength does not decline in 30 days, and the permeability is less than 9.0x10 -3 mD has excellent corrosion resistance and is more helpful in ensuring the sealing integrity of cement sheath in high CO2 environment, providing favorable support for cementing in acidic oil and gas reservoirs.

[0057] In summary, the nano-based carbon dioxide corrosion-resistant cement slurry of the present invention has the excellent properties of adjustable density, low permeability, non-fading strength and corrosion resistance, which effectively solves the problem that cement slurry and cement stone cannot meet the operation requirements under complex formation conditions such as high-concentration CO2 formation cementing, CO2 oil displacement during secondary oil recovery and CO2 storage.

[0058] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A nano-based carbon dioxide corrosion resistant cement slurry, characterized in that The raw materials include, by weight, 100 parts of cement, 5.0 to 10.0 parts of active materials, 5.0 to 20.0 parts of non-permeable materials, 0 to 20.0 parts of lightening materials, 0 to 5.0 parts of weighting materials, 5.0 to 20.0 parts of nano-based inert materials, 10.0 to 30.0 parts of anti-corrosion materials, 5.0 to 6.0 parts of fluid loss additives, 1.0 to 3.0 parts of retarders, 1.0 to 2.0 parts of dispersants, 0.5 to 1.0 parts of defoaming agents, and 43.0 to 64.0 parts of water.

2. The nano-based carbon dioxide corrosion resistant cement slurry according to claim 1, characterized in that The cement is oil well G grade medium sulphur and hydrochloric acid resistant cement; or / and, the active material is microsilica powder with a particle size of 1μm to 20μm; or / and, the non-permeable material is ultrafine cement, which is composed of 50% to 70% by mass of cement with a particle size distribution of 10μm to 15μm and the remainder of cement with a particle size distribution of 30μm to 35μm.

3. The nano-based carbon dioxide corrosion resistant cement slurry according to claim 1 or 2, characterized in that The lightening material is one or more of glass beads, diatoms and soil; or / and, the weighting material is one or more of barite, iron ore powder and manganese oxide.

4. The nano-based carbon dioxide corrosion resistant cement slurry according to claim 1, 2 or 3, characterized in that The nano-based inert material is a mixture of silicon dioxide and graphene oxide in a mass ratio of 45 to 60:40 to 55; or / and, the anti-corrosion material is one or more of sodium borosilicate fiber, latex powder, and rubber.

5. The nano-based carbon dioxide corrosion resistant cement slurry according to any one of claims 1 to 4, characterized in that The fluid loss reducer is one or more of amine-modified humic acid compounds, organosilicon humic acid amide compounds, and sulfonated olefin styrene compounds.

6. The nano-based carbon dioxide corrosion resistant cement slurry according to any one of claims 1 to 5, characterized in that The retarder is one or more of wood sulfonate compounds, hydroxycarboxylic acids and salt compounds thereof.

7. The nano-based carbon dioxide corrosion resistant cement slurry according to any one of claims 1 to 6, characterized in that The dispersant is one or more of formaldehyde acetone condensation product, polynaphthalene sulfonate and amino polymer derivative.

8. The nano-based carbon dioxide corrosion resistant cement slurry according to any one of claims 1 to 7, characterized in that The defoaming agent is one of polyorganosiloxane or organic phosphate.

9. The nano-based carbon dioxide corrosion resistant cement slurry according to any one of claims 1 to 8, characterized in that Obtained as follows: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding a required amount of fluid loss reducer, retarder, dispersant and defoamer to a required amount of water at a stirring speed of 3800 rpm to 4200 rpm and stirring for 50 s to 70 s to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring for 35 seconds to 40 seconds at a stirring speed of 3800 rpm to 4200 rpm to obtain nano-based carbon dioxide corrosion resistant cement slurry.

10. A method for preparing nano-based carbon dioxide corrosion resistant cement slurry according to any one of claims 1 to 8, characterized in that Proceed as follows: S1, fully mixing required amounts of cement, active material, non-permeable material, lightening material, weighting material, nano-based inert material and anti-corrosion material to obtain a solid mixture; S2, adding a required amount of fluid loss reducer, retarder, dispersant and defoamer to a required amount of water at a stirring speed of 3800 rpm to 4200 rpm and stirring for 50 s to 70 s to obtain a mixed solution; S3, adding the solid mixture to the mixed liquid at a uniform speed within 15 seconds, stirring for 35 seconds to 40 seconds at a stirring speed of 3800 rpm to 4200 rpm to obtain nano-based carbon dioxide corrosion resistant cement slurry.